Urban Facility Management Improving Livability through Smart Public Spaces in Smart Sustainable Cities - Shimaa Basheir Abdelkarim (18877117) (2023)
Public spaces play a significant role in improving social, recreational and cultural activities that are inclusive. However, smart public spaces are required to save time and costs, and to provide comfort to the public, ultimately enhancing livability. There are various user requirements and demands to respond to. This research aims to adopt intelligent technologies applied in public spaces to facilitate livability through urban facility management (UFM) involvement in improving livability. The establishment of intelligent systems in the architecture industry goes hand in hand with the growing advancement of science and technology in several aspects of human life. A fundamental key to the success of smart cities is the high quality of livability offered to their residents and visitors. The UFM can enable livability by providing data centers, access controls, integrated security systems, monitoring, smart waste, energy and water management in public spaces. This study focused on five elements of livability, including accessibility, functional infrastructure, interaction and social cohesion, amenity and participation, quality of life through safety and security and privacy. The research methodology adopts the activity theory (AT) as its underpinning theory for the qualitative data collection process (interviews and a workshop) from industry experts in two prominent smart cities in Qatar, Lusail and Msheireb, along with a literature review. This study’s results provide information on existing smart city and public space features, infrastructures and their impact on livability. The findings of this study support the development of the smart livable public spaces (SLiPS) framework. The framework is a baseline for improving livability in smart cities, which allows future updates based on existing ICT infrastructure, enabling new functions and the availability of novel technology applied by UFM. The outcome of livability leads to the achievement of smart city goals. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su152316257